Harnessing Urbanization to End Poverty and Boost Prosperity in Africa - World Bank (World Bank, Washington, DC, 2014)
Urbanization is the single most important transformation that the African continent will undergo this century. More than half of Africa's population will live in its cities by 2040. In the face of rapid urbanization, there is a narrow window of opportunity to harness the potential of cities as engines of economic growth, and use this as a powerful leverage to achieve sustainable development and poverty reduction. Despite its rapid urban growth, Africa is less than halfway through the urbanization process and in some countries, a large number of people reside in rural areas. Rapid urbanization, if well managed, can curb urban sprawl, deteriorating access to services, greater inequality, and increased crime. The concentration of people in cities also elevates the risks and costs associated with extreme weather and natural disasters resulting from climate change. The World Bank Group's (WBGs) support will focus on three key areas: metropolitan areas and large cities; secondary and tertiary cities; and informal settlements. This will include both multi-sectoral investment programs that integrate a basket of services (for example, upgrading of electricity, water, sanitation, roads, drains in unplanned settlements); and sector specific projects (for example, in urban water, solid waste, and transport) to improve the effectiveness of service delivery. This paper is organized in following chapters: chapter one discusses why is it urgent to get Africa's urbanization right?; chapter two gives the vision for efficient, inclusive, and sustainable urbanization; chapter three presents priorities for Africa's policymakers; and chapter four deals with working with Africa to support efficient, inclusive, and sustainable cities.